THE LOST WORLD OF BYZANTIUM - Harris, Jonathan (Yale University Press, 2015)
For more than a millennium, the Byzantine Empire presided over the juncture between East and West, as well as the transition from the classical to the modern world. Jonathan Harris, a leading scholar of Byzantium, eschews the usual run-through of emperors and battles and instead recounts the empire's extraordinary history by focusing each chronological chapter on an archetypal figure, family, place, or event. Harris's action-packed introduction presents a civilization rich in contrasts, combining orthodox Christianity with paganism, and classical Greek learning with Roman power. Frequently assailed by numerous armies--including those of Islam--Byzantium nonetheless survived and even flourished by dint of its somewhat unorthodox foreign policy and its sumptuous art and architecture, which helped to embed a deep sense of Byzantine identity in its people. Enormously engaging and utilizing a wealth of sources to cover all major aspects of the empire's social, political, military, religious, cultural, and artistic history, Harris's study illuminates the very heart of Byzantine civilization and explores its remarkable and lasting influence on its neighbors and on the modern world